KARAKTERISASI NATRIUM ALGINAT DARI Sargassum sp., Turbinaria sp. DAN Padina sp. [Characterization of Sodium Alginate from Sargassum sp., Turbinaria sp. and Padina sp.] - Wahyu - Mushollaeni; Endang - Rusdiana (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
This study aimed to obtain characteristics of Na-alginate from brown seaweeds. The characteristics studied include chemical, physical parameters and its functional group by FTIR. The brown seaweeds were S. crassifolium, S. polycystum, Padina australis, S. echinocarpum, S. duplicatum, S. binderi, T. conoides, T. decurrens, growing on the coral coast of Gunung Kidul Yogyakarta. Thewater content, ash content, purity, and also Pb and Hg were 12.50-13.43%; 18.20-28.59%; 15.86-28.80%; 0.083±0.01-0.36±0.04 ppm and 0.002±0.01-0.3±0.,05 ppm respectively. Physical properties of the alginate, i.e viscosity and lightness were 25-39 cps and 46.2-52.3 (yellow to light brown), respectively the average yield was 16.93-30.50%. The FTIR analysis showed that Na-alginate of the samples and standard had the same functional group.